Calcium orthophosphates (CaPO(4)): occurrence and properties - Dorozhkin, Sergey V. (Prog Biomater, 2015)
The present overview is intended to point the readers’ attention to the important subject of calcium orthophosphates (CaPO(4)). This type of materials is of the special significance for the human beings because they represent the inorganic part of major normal (bones, teeth and antlers) and pathological (i.e., those appearing due to various diseases) calcified tissues of mammals. For example, atherosclerosis results in blood vessel blockage caused by a solid composite of cholesterol with CaPO(4), while dental caries and osteoporosis mean a partial decalcification of teeth and bones, respectively, that results in replacement of a less soluble and harder biological apatite by more soluble and softer calcium hydrogenorthophosphates. Therefore, the processes of both normal and pathological calcifications are just an in vivo crystallization of CaPO(4). Similarly, dental caries and osteoporosis might be considered as in vivo dissolution of CaPO(4). In addition, natural CaPO(4) are the major source of phosphorus, which is used to produce agricultural fertilizers, detergents and various phosphorus-containing chemicals. Thus, there is a great significance of CaPO(4) for the humankind and, in this paper, an overview on the current knowledge on this subject is provided.